(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The intense usage of celebrity endorsement as a tool ofadvertising strategy has increased drastically in the past few years;celebrities have been used to promote various kinds of products and services,from sports to beverages to all kinds of electronics and several otherproducts. The drastic rise of celebrity endorsers is not limited to a specificsector of the economy, companies using celebrity endorsement cut across allindustry categories –including packaged goods, telecommunication, financialservices and automobile industries (Thompson, 1998, Okorie, 2010; Okorie &Aderogba, 2011).